2021
DOI: 10.1364/boe.425527
|View full text |Cite
|
Sign up to set email alerts
|

High frame rate video mosaicking microendoscope to image large regions of intact tissue with subcellular resolution

Abstract: High-resolution microendoscopy (HRME) is a low-cost strategy to acquire images of intact tissue with subcellular resolution at frame rates ranging from 11 to 18 fps. Current HRME imaging strategies are limited by the small microendoscope field of view (∼0.5 mm2); multiple images must be acquired and reliably registered to assess large regions of clinical interest. Image mosaics have been assembled from co-registered frames of video acquired as a microendoscope is slowly moved across the tissue surface, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The high frame rate of the microscope and the large percentage of overlap between subsequent frames enables detection of subtle changes in cellular morphology at the surface of the epithelium. We have previously shown that this high frame rate combined with image analysis techniques can effectively increase the eld of view of the microscope through the generation of high-quality mosaics 27 . While these large mosaics can be used to directly visualize large areas of the epithelium, previous implementations were unable to provide diagnostic guidance based on these generated mosaics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high frame rate of the microscope and the large percentage of overlap between subsequent frames enables detection of subtle changes in cellular morphology at the surface of the epithelium. We have previously shown that this high frame rate combined with image analysis techniques can effectively increase the eld of view of the microscope through the generation of high-quality mosaics 27 . While these large mosaics can be used to directly visualize large areas of the epithelium, previous implementations were unable to provide diagnostic guidance based on these generated mosaics.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaic Generation. High resolution mosaics were generated using a previously described approach 27 . Brie y, the region of the image corresponding to the active area of the ber bundle is identi ed and all frames are downsampled to remove the ber bundle pattern from the image.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ABGS consists of two subsystems controlled through a single user interface: (1) a camera and projector for white light (WL) and AF image acquisition and real-time projection of visible risk maps and (2) a microscope with a fiber optic probe to image nuclear morphology. 21 The ABGS is designed to guide a clinician through widefield and microscopic imaging to determine if and where a biopsy is needed for early detection of oral cancer and its precursors. Figure 1(a) shows a photograph of the ABGS system; the camera and projector are assembled and housed in a 3D-printed enclosure and mounted on a portable articulated arm.…”
Section: Methodsmentioning
confidence: 99%